Insights Into Atorvastatin Pharmacokinetics in Rats Reveal Regulation of CYP3A1 by Humanization of SLCO2B1 - Jonny Kinzi; Janine Hussner; Isabell Seibert; Marta Rysz; Valerio Taggi; Simone Zuercher; Annika Tillmann; Oliver Schwardt; Stefan Oswald; Daniel Ricklin; Henriette E. Meyer zu Schwabedissen (Pharmacology Research & Perspectives)
ABSTRACT The organic anion transporting polypeptide (OATP) 2B1 is expressed in pharmacokinetically relevant organs such as the liver, the kidney, and the small intestine and it is known to transport a broad range of substrates including statins. In pharmacokinetic studies applying two rat models—one deficient for rat Oatp2b1 and the other expressing the human transporter—we investigated the disposition of atorvastatin, a known OATP2B1 substrate, and observed a reduced exposure and an increased clearance of this OATP2B1 substrate in humanized rats compared to knockout animals. Atorvastatin is predominantly cleared via the bile and due to the clearance increase, we assessed hepatic accumulation of this OATP2B1 substrate. Blood and organs were collected 1 h after administration of the HMG‐CoA reductase inhibitor via tail vein injection. Sample analysis revealed lower drug concentrations in serum but also 40% lower hepatic atorvastatin levels in SLCO2B1‐humanized rats compared to knockout animals, despite the expected role of OATP2B1 in facilitating hepatocellular uptake. Expression analysis of other drug transporters involved in hepatocellular handling of atorvastatin in treatment‐naive rats revealed no differences in the sinusoidal uptake transporter rOatp1b2 and the canalicular efflux transporters rBcrp and rMdr1a between genotypes. However, transcript and protein analysis of rCyp3a1 in liver tissues showed approximately 3‐fold higher levels in SLCO2B1‐humanized rats compared to rSlco2b1‐knockout animals. The increase in rCyp3a1 levels likely reflects an enhanced metabolic rate leading to lower hepatic atorvastatin content. Our finding suggests that humanization of OATP2B1 might influence hepatic disposition of rCyp3a1 substrates.